In focus: perplexing increase of urinary stone disease in children, adolescent and young adult women and its economic impact - Filler, Guido; Dave, Sumit; Ritter, Victor; Ross, Sherry; Viprakasit, Davis; Hatch, Joseph E.; Bjazevic, Jennifer; Burton, Jeremy; Gilleskie, Donna; Gilliland, Jason; Lin, Feng-Chang; Jain, Nina; et al. (Frontiers in Medicine, 2023)
Evidence before this study Urinary stone disease (USD) is increasing around the world. It used to be a disease of older overweight men owing to lower urine pH and a lower post-prandial absorption of anions. However, the incidence of USD has shifted to women with the fastest increase in adolescents and young adults (AYA). The reasons for this phenomenon are unclear. Added value of this study We describe the changing epidemiological trends and sex differences of USD in the province of Ontario, Canada over a 15-year-period as well as in a single center in North Carolina, United States of America over a 5-year-period. We illustrate the pathophysiological differences in USD between men and women and discuss possible etiologies including microplastics as possible nidus of USD. Microplastics are metabolized by the kidneys and there is a 3-fold difference between women and men with regards to the formation of insoluble mono-butyl-phthalate. We also offer suggestions for future research to understand this perplexing sex difference. Implications of this study The incidence of USD has shifted to more women and younger patients, and in fact may become more prevalent than diabetes mellitus. USD is associated with great morbidity and has the potential for chronic kidney disease later in life. Effective strategies to prevent and treat USD need to be developed. The growing public health problem of USD in younger patients requires research efforts to understand the sex differences and to design interventions.